Peran Front Office Department dalam Meningkatkan Kualitas Pelayanan Check In dan Check Out Tamu di Hotel Banjar Permai Kota Banjarbaru Kalimantan Selatan - Octavia, Zilla Arum; Fadhillah, Is (As-Syirkah: Islamic Economic & Financial Journal, 2024)
This research was conducted to find out more about "The Role of the Front Office Department in Improving the Quality of Guest Check In and Check Out Services at the Banjar Permai Hotel, Banjarbaru City, South Kalimantan" which was motivated by the decline in guest arrival rates during the Covid-19 period and currently continues and try to stabilize occupancy by improving service quality. This research uses a qualitative approach, with the subjects are employees of the Front Office Department, Supervisors, and overnight guests as purposive sampling material. The Data was obtained through interviews, observation and documentation, which was then carried out through descriptive qualitative analysis. The results of this research are: 1) The role of the Front Office Department in improving the quality of check-in and check-out services must follow existing service standards and must provide service that exceeds the expectations of an overnight guest and creates a good first and last impression. so that it results in customer satisfaction and customer loyalty in the future. 2) Various obstacles that occur in the check-in service process, namely; guests do not want to provide identification, impatient guests, while checking out; guests leaving the room without announce, room keys being taken away by guests, lost hotel items, and so on. All of this is stated in full in the researcher's thesis.  3) Solutions in facing all obstacles can be overcome by each Front Office because they have been accustomed to and learning from each other, apart from that there are clear rules and firm actions but still adhering to the value of politeness in dealing with guests which is the main value in the quality of service provided guarded by a Front Office. Every obstacle that occurs is always evaluated in monthly meetings for the Front Office Department and upper levels so that good service can be improved and create satisfaction for each customer and have an impact on the progress of the Banjar Permai Hotel in the future.